Seasonal bleaching and partial mortality of Pocillopora verrucosa corals of the coast of central Vietnam - Lishchenko, Fedor V.; Burmistrova, Yuliya A.; Petrochenko, Roman A.; Nguyen, Thanh H.; Britayev, Temir A. (Frontiers in Marine Science, 2024)
Coral reefs are one of the most productive yet vulnerable ecosystems on Earth. An important step in understanding the functioning of coral communities is studying the environmental impact on the state of reefs. The present study aimed to assess the impacts of the water temperature, precipitation, wave action, and population density on the seasonal bleaching, partial and complete mortality of shallowwater branching corals of Pocillopora verrucosa species complex. The present study was conducted at the Dam Bay research station (Nha Trang Bay) from 26 April 2020 to 2 April 2021. The environmental data was collected from the Dam Bay weather station and using a temperature logger planted on the nursery, coral bleaching and mortality were assessed visually using photos taken underwater. Throughout the study, the percentage of bleached coral colonies varied from 1 to 41.5% with two peaks, in autumn (October) and spring (April). Rates of the development of partial mortality varied from 0 to 10%, with a pronounced peak in December. At the end of the experiment, the percentage of coral colonies suffering from partial mortality reached 47%. Only 4,5% of experimental colonies died to the end of the study. Analysis revealed that water temperature and partial mortality are the drivers of bleaching, while wave action, temperature and bleaching are the factors with a significant impact on partial mortality. Thus, both bleaching and patrial mortality are interlinked and the effect of partial mortality on bleaching is stronger than the opposite. Both phenomena have pronounced seasonal variation, but their maximum manifestation does not coincide in time allowing corals to avoid their synergetic effect. Moreover, it was found that the impact of individual stress on mortality prevailed over the impact of seasonal bleaching and partial mortality events. The main cause of coral death was the development of algal fouling at the sites of colony lesions, which gradually spread over the entire surface of the colony.